PENGARUH PENGGUNAAN TANAH MEDITERAN SEBAGAI BAHAN SUBSTITUSI SEMEN TERHADAP KUAT TEKAN DAN TARIK BETON - Nilawardani, Sri Devi (ATRIUM: Jurnal Arsitektur, 2019)
Title: The Effect of Using Mediteran Soil as Cement Substitution Materials in Compressive Strength and Tensile Strength of Concrete Concrete is a composite material (mixture) of cement, fine aggregate, coarse aggregate, and water. The potential of limestone in Indonesia is very large, reaching 28.678 billion tons which is the main ingredient in the cement manufacture. In the long run it will be depleted because it is a non-renewable natural resources. So to reduce the use of limestone the utilization of Mediteran soil as a substitution for some cement in the manufacture of concrete is required. The initial idea is based on the chemical composition contained in the Mediteran soil almost identical to the cement, which is carbonate (CaO) and silica (SiO2). The purpose of this research is to reveal the influence of substitution of Mediteran soil by 20% and 40% in the compressive strength and tensile of the concrete at age 3, 7, 14, and 28 days with the number of test specimen each 3 pieces on each variation in 10cm x20cm cylinder with planning of concrete mixture refers to SK SNI method T-15-1900-03. The type of research used is quantitative with the experimental method of laboratory test and data analysis of comparative method and regression. The results show that compressive strength and tensile strength of concrete using Mediteran soil substitution comparable toÂ  the strength of normal concrete with dry treatment. In the composition of 20% Mediteran soils decreased by 51.35% or 7.9 MPa (compressive strength) and 30.60% or 0.93 MPa (tensile strength). While the composition of 40% Mediteran soil decreased by 43.78% or 9.13 MPa (compressive strength) and 2.24% or 1.31 MPa (tensile strength). Â